Influence of lactic fermentation (bokashi fertilizer) in the pre-compost for biogas and organic fertilizer production in batch digesters - Torres Torres, Allen (2015)
The research study named “Influence of lactic fermentation (bokashi fertilizer) in the pre-compost for biogas and organic fertilizer production in batch digesters” approaches as a solution to treatment before placing solid wastes in the anaerobic reactors and there by improve the quality of the products generated: biogas and organic fertilizer.The research began in August 2012, using batch anaerobic reactors for three treatments. For the three treatments we used the same substrate was cow manure. The variation between the three treatments consisted of treatment before use: Treatment 1 was placed anaerobic reactors substrate without pretreatment, Treatment 2 was performed pre- composting to the substrate before placing the anaerobic reactor, and Treatment 3 was performed as pretreatment bokashi compost before placing the anaerobic reactor, bokashi was developed with beneficial microorganisms which act on the substrate by make treatment more efficient in less time. This research aimed to compare between the three treatments the quality and quantity of biogas as organic fertilizer. For biogas quality, Treatment 1reached an average concentration of 50.7 % of methane, Treatment 2 reached an average of 52.6 % and Treatment 3 reached an average of 50.9 %. For biogas volume Treatment 3 obtained a production of 0.2 m3/kg VS, Treatment 2 obtained a production of 0.15 m /kg vs, and Treatment 1 obtained a production of 0.1 m3/kg VS. The organic fertilizer obtained in Treatment 3 has higher concentration of macronutrients and fewer pathogens in compared to Treatment 2 and Treatment 1, making the organic fertilizer in the Treatment 3 the highest quality.